Implementasi Kebijakan Elektronifikasi Transaksi Pemerintah Daerah (ETPD) dalam Mewujudkan Keuangan Digital di Pemerintah Kota Padang - Putri, Rhaisa Indira; Helmi, Ramadhona Fitri (Lembaga Yasin AlSys, 2025)
The implementation of the Regional Government Transaction Electronification (ETPD) policy represents a strategic step in supporting digital financial transformation within government institutions. However, its execution still faces various technical and institutional challenges. This study aims to describe the implementation of the ETPD policy in the Padang City Government and to identify the supporting and inhibiting factors influencing the process. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation. Data analysis refers to Edward III’s policy implementation theory, which includes four key variables: communication, resources, disposition, and bureaucratic structure. The findings indicate that the ETPD implementation in Padang City has progressed fairly well, as evidenced by the establishment of the Regional Digitalization Acceleration and Expansion Task Force (TP2DD), enhanced digital infrastructure, and training and outreach initiatives supported by Bank Indonesia and related institutions. Nonetheless, several obstacles persist, such as the lack of comprehensive leadership commitment, weak inter-agency coordination, limited technical regulations, low public digital literacy, and uneven dissemination efforts. The study concludes that optimizing ETPD implementation in Padang City requires strengthening human resource capacity, developing technical standard operating procedures, and enhancing cross-sector collaboration to realize a transparent, effective, and accountable digital financial system.